An extension of the arden syntax to facilitate clinical document generation - Kraus, Stefan; Toddenroth, Dennis; Unberath, Philipp; Prokosch, Hans-Ulrich; Hueske-Kraus, Dirk (Healthcare of the Future - Bridging the Information Gap, 2019)
While clinical information systems usually store patient records in database tables, human interpretations as well as information transfer between institutions often require that clinical data can be represented as documents. To automate document generation from patient data in conjunction with the rich computational facilities of clinical decision support, we propose a template-based extension of the Arden Syntax, and discuss the benefits and limitations observed during a pilot application for patient recruitment. While the original Arden Syntax supports string concatenation as well as the substitution of unnamed placeholders, we integrated an additional method based on embedding expressions into strings. A dedicated parser identifies the expressions and automatically substitutes them at runtime, which can for example be harnessed to display the most recent value from a time series. The resulting mechanism supports the generation of extensive clinical documents without the need to apply specific operators. To evaluate the proposed extension, we implemented an Arden module that identifies an intensive care patient cohort that conforms to the eligibility criteria of a clinical trial and outputs a concise patient overview in different document formats. While string interpolation in the original Arden standard has been tailored to clinical event monitoring, we interpret that our accessible approach usefully extends Arden's data-to-text capabilities. Future research might target the development of an interactive template editor that would hide the complexity of formatting directives and conditional expressions behind a graphical user interface, and explore how computer-linguistic formalisms might facilitate advanced features such as automatic inflections of verbs and nouns.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Arden Syntax; Clinical document generation; Natural language generation; String interpolation

An Extension of the Arden Syntax to Facilitate Clinical Document Generation. - Kraus, Stefan; Toddenroth, Dennis; Unberath, Philipp; Prokosch, Hans-Ulrich; Hueske-Kraus, Dirk (ICT for Health Science Research, 2019)
While clinical information systems usually store patient records in database tables, human interpretations as well as information transfer between institutions often require that clinical data can be represented as documents. To automate document generation from patient data in conjunction with the rich computational facilities of clinical decision support, we propose a template-based extension of the Arden Syntax, and discuss the benefits and limitations observed during a pilot application for patient recruitment. While the original Arden Syntax supports string concatenation as well as the substitution of unnamed placeholders, we integrated an additional method based on embedding expressions into strings. A dedicated parser identifies the expressions and automatically substitutes them at runtime, which can for example be harnessed to display the most recent value from a time series. The resulting mechanism supports the generation of extensive clinical documents without the need to apply specific operators. To evaluate the proposed extension, we implemented an Arden module that identifies an intensive care patient cohort that conforms to the eligibility criteria of a clinical trial and outputs a concise patient overview in different document formats. While string interpolation in the original Arden standard has been tailored to clinical event monitoring, we interpret that our accessible approach usefully extends Arden's data-to-text capabilities. Future research might target the development of an interactive template editor that would hide the complexity of formatting directives and conditional expressions behind a graphical user interface, and explore how computer-linguistic formalisms might facilitate advanced features such as automatic inflections of verbs and nouns.
EVALuna2:209495

A REST Service for the Visualization of Clinical Time Series Data in the Context of Clinical Decision Support. - Unberath, Philipp; Prokosch, Hans-Ulrich; Kraus, Stefan (ICT for Health Science Research, 2019)
BACKGROUND: University Hospital Erlangen provides clinical decision support (CDS) functions in the intensive care setting, that are based on the Arden Syntax standard. These CDS functions generate extensive output, including patient data charts. In the course of the migration of our CDS platform we revised the charting tool because although the tool was generally perceived as useful, the clinical users reported several shortcomings. OBJECTIVE: During the migration of our CDS platform, we aimed at resolving the reported shortcomings and at developing a reusable and parameterizable charting tool, driven by best practices and requirements of local clinicians. METHODS: We conducted a requirements analysis with local clinicians and searched the literature for well-established guidelines for clinical charts. Using a charting library, we then implemented the tool based on the found criteria and provided it with a REST interface. RESULTS: The criteria catalog included 18 requirements, all of which were successfully implemented. The new charting tool fully replaced the previous implementation in clinical routine. It also provides a web interface that enables clinicians to configure charts without programming skills. CONCLUSION: The new charting tool combines local preferences with best practices for visualization of clinical time series data. With its REST interface and reusable design it can be easily integrated in existing CDS platforms.
EVALuna2:209494

A REST service for the visualization of clinical time series data in the context of clinical decision support - Unberath, Philipp; Prokosch, Hans-Ulrich; Kraus, Stefan (Proceedings of the EFMI 2019 Special Topic Conference, 2019)
Background: University Hospital Erlangen provides clinical decision support (CDS) functions in the intensive care setting, that are based on the Arden Syntax standard. These CDS functions generate extensive output, including patient data charts. In the course of the migration of our CDS platform we revised the charting tool because although the tool was generally perceived as useful, the clinical users reported several shortcomings. Objective: During the migration of our CDS platform, we aimed at resolving the reported shortcomings and at developing a reusable and parameterizable charting tool, driven by best practices and requirements of local clinicians. Methods: We conducted a requirements analysis with local clinicians and searched the literature for well-established guidelines for clinical charts. Using a charting library, we then implemented the tool based on the found criteria and provided it with a REST interface. Results: The criteria catalog included 18 requirements, all of which were successfully implemented. The new charting tool fully replaced the previous implementation in clinical routine. It also provides a web interface that enables clinicians to configure charts without programming skills. Conclusion: The new charting tool combines local preferences with best practices for visualization of clinical time series data. With its REST interface and reusable design it can be easily integrated in existing CDS platforms.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Clinical decision support; Patient data charts; Visualization

A toolbox for functional analysis and the systematic identification of diagnostic and prognostic gene expression signatures combining meta-analysis and machine learning - Vey, Johannes; Kapsner, Lorenz; Fuchs, Maximilian; Unberath, Philipp; Veronesi, Giulia; Kunz, Meik (Cancers, 2019)
The identification of biomarker signatures is important for cancer diagnosis and prognosis. However, the detection of clinical reliable signatures is influenced by limited data availability, which may restrict statistical power. Moreover, methods for integration of large sample cohorts and signature identification are limited. We present a step-by-step computational protocol for functional gene expression analysis and the identification of diagnostic and prognostic signatures by combining meta-analysis with machine learning and survival analysis. The novelty of the toolbox lies in its all-in-one functionality, generic design, and modularity. It is exemplified for lung cancer, including a comprehensive evaluation using different validation strategies. However, the protocol is not restricted to specific disease types and can therefore be used by a broad community. The accompanying R package vignette runs in 1 h and describes the workflow in detail for use by researchers with limited bioinformatics training.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Bioinformatics tool; Biomarker signature; Functional analysis; Gene expression analysis; Machine learning; Meta-analysis; R package; Survival analysis

Automated whole exome sequencing analysis pipeline to support a molecular tumor board - Metzger, P.; Hess, M.; Jaravine,; Boeker, M.; Christoph, Jan; Unberath, Philipp; Busch, H.; Andrieux, G.; Boerries, M. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

cbpManager: a web application to streamline the integration of clinical and genomic data in cBioPortal to support the Molecular Tumor Board - Ustjanzew, Arsenij; Desuki, Alexander; Ritzel, Christoph; Dolezilek, Alina Corinna; Wagner, Daniel-Christoph; Christoph, Jan; Unberath, Philipp; Kindler, Thomas; Faber, Jorg; Marini, Federico; Panholzer, Torsten; Paret, Claudia (BMC Medical Informatics and Decision Making, 2021)
Background: Extensive sequencing of tumor tissues has greatly improved our understanding of cancer biology over the past years. The integration of genomic and clinical data is increasingly used to select personalized therapies in dedicated tumor boards (Molecular Tumor Boards) or to identify patients for basket studies. Genomic alterations and clinical information can be stored, integrated and visualized in the open-access resource cBioPortal for Cancer Genomics. cBioPortal can be run as a local instance enabling storage and analysis of patient data in single institutions, in the respect of data privacy. However, uploading clinical input data and genetic aberrations requires the elaboration of multiple data files and specific data formats, which makes it difficult to integrate this system into clinical practice. To solve this problem, we developed cbpManager. Results: cbpManager is an R package providing a web-based interactive graphical user interface intended to facilitate the maintenance of mutations data and clinical data, including patient and sample information, as well as timeline data. cbpManager enables a large spectrum of researchers and physicians, regardless of their informatics skills to intuitively create data files ready for upload in cBioPortal for Cancer Genomics on a daily basis or in batch. Due to its modular structure based on R Shiny, further data formats such as copy number and fusion data can be covered in future versions. Further, we provide cbpManager as a containerized solution, enabling a straightforward large-scale deployment in clinical systems and secure access in combination with ShinyProxy. cbpManager is freely available via the Bioconductor project at https://bioconductor.org/packages/cbpManager/ under the AGPL-3 license. It is already used at six University Hospitals in Germany (Mainz, Gießen, Lübeck, Halle, Freiburg, and Marburg). Conclusion: In summary, our package cbpManager is currently a unique software solution in the workflow with cBioPortal for Cancer Genomics, to assist the user in the interactive generation and management of study files suited for the later upload in cBioPortal.
CRIS-Team Scopus Importer:2021-12-31
Keywords: Bioconductor; cBioPortal; Clinical data; Data management; File generation; Genomic data; Molecular Tumor Board; Patient management; R; Shiny

Challenges and Experiences Extending the cBioPortal for Cancer Genomics to a Molecular Tumor Board Platform. - Reimer, Niklas; Unberath, Philipp; Busch, Hauke; Börries, Melanie; Metzger, Patrick; Ustjanzew, Arsenij; Renner, Christopher; Prokosch, Hans-Ulrich; Christoph, Jan (Studies in health technology and informatics, 2021)
In Molecular Tumor Boards (MTBs), therapy recommendations for cancer patients are discussed. To aid decision-making based on the patient's molecular profile, the research platform cBioPortal was extended based on users' requirements. Additionally, a comprehensive dockerized workflow was developed to support the deployment of cBioPortal and connected services. In this work, we present the challenges and experiences of nearly two years of implementing and deploying an MTB platform based on cBioPortal and compare those to findings of a previous study.
EVALuna2:512349

Critical evaluation of molecular tumour board outcomes following 2 years of clinical practice in a Comprehensive Cancer Centre - Scheiter, Alexander; Hierl, Frederik; Lueke, Florian; Keil, Felix; Heudobler, Daniel; Einhell, Sabine; Klier-Richter, Margit; Konstandin, Nikola P.; Weber, Florian; Scheiter, Andrea; Kandulski, Arne; Schlosser, Sophie; et al. (British Journal of Cancer, 2022)
BACKGROUND: Recently, molecular tumour boards (MTBs) have been integrated into the clinical routine. Since their benefit remains debated, we assessed MTB outcomes in the Comprehensive Cancer Center Ostbayern (CCCO) from 2019 to 2021. METHODS AND RESULTS: In total, 251 patients were included. Targeted sequencing was performed with PCR MSI-evaluation and immunohistochemistry for PD-L1, Her2, and mismatch repair enzymes. 125 treatment recommendations were given (49.8%). High-recommendation rates were achieved for intrahepatic cholangiocarcinoma (20/30, 66.7%) and gastric adenocarcinoma (10/16, 62.5%) as opposed to colorectal cancer (9/36, 25.0%) and pancreatic cancer (3/18, 16.7%). MTB therapies were administered in 47 (18.7%) patients, while 53 (21.1%) received alternative treatment regimens. Thus 37.6% of recommended MTB therapies were implemented (47/125 recommendations). The clinical benefit rate (complete + partial + mixed response + stable disease) was 50.0% for MTB and 63.8% for alternative treatments. PFS2/1 ratios were 34.6% and 16.1%, respectively. Significantly improved PFS could be achieved for m1A-tier-evidence-based MTB therapies (median 6.30 months) compared to alternative treatments (median 2.83 months; P = 0.0278). CONCLUSION: The CCCO MTB yielded a considerable recommendation rate, particularly in cholangiocarcinoma patients. The discrepancy between the low-recommendation rates in colorectal and pancreatic cancer suggests the necessity of a weighted prioritisation of entities. High-tier recommendations should be implemented predominantly.
CRIS-Team WoS Importer:2023-01-27

Developing New Analysis Functions for a Translational Research Platform: Extending the cBioPortal for Cancer Genomics. - Unberath, Philipp; Knell, Christian; Prokosch, Hans-Ulrich; Christoph, Jan (ICT for Health Science Research, 2019)
BACKGROUND: The cBioPortal is a prevalent open-source translational research platform, allowing private instances and extensions. OBJECTIVE: Our aim was to build up an own instance of cBioPortal, identify missing functionality by interviewing researchers, and implementing these extensions. METHODS: We examined the code base of the cBioPortal and conducted a requirements analysis with researchers. Then an own extension was implemented and a usability evaluation was performed. RESULTS: We developed a new tab in the results view of cBioPortal adding the option to analyze the correlation of gene expression and mutation patterns. CONCLUSION: While extending the cBioPortal is possible, there are still some challenges to overcome. A plug-in concept and a more detailed documentation would greatly facilitate the development of own extensions.
EVALuna2:209492

Developing new analysis functions for a translational research platform: Extending the cBioPortal for cancer genomics - Unberath, Philipp; Knell, Christian; Prokosch, Hans-Ulrich; Christoph, Jan (Proceedings of the EFMI 2019 Special Topic Conference, 2019)
Background: The cBioPortal is a prevalent open-source translational research platform, allowing private instances and extensions. Objective: Our aim was to build up an own instance of cBioPortal, identify missing functionality by interviewing researchers, and implementing these extensions. Methods: We examined the code base of the cBioPortal and conducted a requirements analysis with researchers. Then an own extension was implemented and a usability evaluation was performed. Results: We developed a new tab in the results view of cBioPortal adding the option to analyze the correlation of gene expression and mutation patterns. Conclusion: While extending the cBioPortal is possible, there are still some challenges to overcome. A plug-in concept and a more detailed documentation would greatly facilitate the development of own extensions.
CRIS-Team Scopus Importer:2019-05-09
Keywords: cBioPortal; Genomics; MI-I; MIRACUM; Translational research

EHR-Independent Predictive Decision Support Architecture Based on OMOP - Unberath, Philipp; Prokosch, Hans-Ulrich; Gründner, Julian; Erpenbeck, Marcel; Maier, Christian; Christoph, Jan (Applied Clinical Informatics, 2020)
BACKGROUND: The increasing availability of molecular and clinical data of cancer patients combined with novel machine learning techniques has the potential to enhance clinical decision support, example, for assessing a patient's relapse risk. While these prediction models often produce promising results, a deployment in clinical settings is rarely pursued. OBJECTIVES: In this study, we demonstrate how prediction tools can be integrated generically into a clinical setting and provide an exemplary use case for predicting relapse risk in melanoma patients. METHODS: To make the decision support architecture independent of the electronic health record (EHR) and transferable to different hospital environments, it was based on the widely used Observational Medical Outcomes Partnership (OMOP) common data model (CDM) rather than on a proprietary EHR data structure. The usability of our exemplary implementation was evaluated by means of conducting user interviews including the thinking-aloud protocol and the system usability scale (SUS) questionnaire. RESULTS: An extract-transform-load process was developed to extract relevant clinical and molecular data from their original sources and map them to OMOP. Further, the OMOP WebAPI was adapted to retrieve all data for a single patient and transfer them into the decision support Web application for enabling physicians to easily consult the prediction service including monitoring of transferred data. The evaluation of the application resulted in a SUS score of 86.7. CONCLUSION: This work proposes an EHR-independent means of integrating prediction models for deployment in clinical settings, utilizing the OMOP CDM. The usability evaluation revealed that the application is generally suitable for routine use while also illustrating small aspects for improvement.
CRIS-Team Scopus Importer:2020-06-16

Empowering personalized oncology: evolution of digital support and visualization tools for molecular tumor boards. - Strantz, Cosima; Böhm, Dominik; Ganslandt, Thomas; Börries, Melanie; Metzger, Patrick; Pauli, Thomas; Blaumeiser, Andreas; Scheiter, Alexander; Jung, Ian Christopher; Christoph, Jan; Manuilova, Iryna; Strauch, Konstantin; et al. (BMC Medical Informatics and Decision Making, 2025)
BACKGROUND: Molecular tumor boards (MTBs) play a pivotal role in personalized oncology, leveraging complex data sets to tailor therapy for cancer patients. The integration of digital support and visualization tools is essential in this rapidly evolving field facing fast-growing data and changing clinical processes. This study addresses the gap in understanding the evolution of software and visualization needs within MTBs and evaluates the current state of digital support. Alignment between user requirements and software development is crucial to avoid waste of resources and maintain trust. METHODS: In two consecutive nationwide medical informatics projects in Germany, surveys and expert interviews were conducted as stage 1 (n = 14), stage 2 (n = 30), and stage 3 (n = 9). Surveys, via the SoSci Survey tool, covered participants' roles, working methods, and support needs. The second survey additionally addressed requirements for visualization solutions in molecular tumor boards. These aimed to understand diverse requirements for preparation, implementation, and documentation. Nine semi-structured expert interviews complemented quantitative findings through open discussion. RESULTS: Using quantitative and qualitative analyses, we show that existing digital tools may improve therapy recommendations and streamline MTB case preparation, while continuous training and system improvements are needed. CONCLUSIONS: Our study contributes to the field by highlighting the importance of developing user-centric, customizable software solutions that can adapt to the fast-paced environment of MTBs to advance personalized oncology. In doing so, it lays the foundation for further advances in personalized medicine in oncology and points to a shift towards more efficient, technology-driven clinical decision-making processes. This research not only enriches our understanding of the integration of digital tools into MTBs, but also signals a broader shift towards technological innovation in healthcare.
EVALuna2:583671

Extending cBioPortal for Therapy Recommendation Documentation in Molecular Tumor Boards: Development and Usability Study - Renner, Christopher; Reimer, Niklas; Christoph, Jan; Busch, Hauke; Metzger, Patrick; Boerries, Melanie; Ustjanzew, Arsenij; Boehm, Dominik; Unberath, Philipp (JMIR Medical Informatics, 2023)
Background: In molecular tumor boards (MTBs), patients with rare or advanced cancers are discussed by a multidisciplinary team of health care professionals. Software support for MTBs is lacking; in particular, tools for preparing and documenting MTB therapy recommendations need to be developed. Objective: We aimed to implement an extension to cBioPortal to provide a tool for the documentation of therapy recommendations from MTB sessions in a secure and standardized manner. The developed extension should be embedded in the patient view of cBioPortal to enable easy documentation during MTB sessions. The resulting architecture for storing therapy recommendations should be integrable into various hospital information systems. Methods: On the basis of a requirements analysis and technology analysis for authentication techniques, a prototype was developed and iteratively refined through a user-centered development process. In conclusion, the tool was evaluated via a usability evaluation, including interviews, structured questionnaires, and the System Usability Scale. Results: The patient view of cBioPortal was extended with a new tab that enables users to document MTB sessions and therapy recommendations. The role-based access control was expanded to allow for a finer distinction among the rights to view, edit, and delete data. The usability evaluation showed overall good usability and a System Usability Scale score of 83.57. Conclusions: This study demonstrates how cBioPortal can be extended to not only visualize MTB patient data but also be used as a documentation platform for therapy recommendations.
CRIS-Team Scopus Importer:2024-12-16
Keywords: cancer; cBioPortal; development; documentation platform; genomics; health information interoperability; implementation; molecular tumor board; platform; precision; precision medicine; tool; tumor; usability evaluation; use; user-centered

FhirSpark - Implementing a Mediation Layer to Bring FHIR to the cBioPortal for Cancer Genomics - Reimer, Niklas; Unberath, Philipp; Busch, Hauke; Ingenerf, Josef (Public Health and Informatics, 2021)
cBioPortal is a commonly used data warehousing solution for genomic cancer studies. The software is being extended for patient care application in a molecular tumor board by the MIRACUM consortium within the Medical Informatics Initiative Germany. A key feature for this use case is the ability to enter therapy recommendations for individual patients, which requires interoperability with the hospital information system. A RESTful interface between cBioPortal and an external mediation layer was selected from the different implementation options. It achieves interoperability by using a FHIR capable server to store data and applying the HL7 FHIR Genomics Reporting implementation guide. For systems not supporting the FHIR standard, the well-established HL7 Version 2 standard is available as a fallback export format.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cBioPortal; Health Information Interoperability; HL7 FHIR; Precision Medicine

Identifications of Similarity Metrics for Patients With Cancer: Protocol for a Scoping Review - Manuilova, Iryna; Bossenz, Jan; Weise, Annemarie Bianka; Böhm, Dominik; Strantz, Cosima; Unberath, Philipp; Reimer, Niklas; Metzger, Patrick; Pauli, Thomas; Werle, Silke D.; Schulze, Susann; Hiemer, Sonja; et al. (JMIR Research Protocols, 2024)
Background: Understanding the similarities of patients with cancer is essential to advancing personalized medicine, improving patient outcomes, and developing more effective and individualized treatments. It enables researchers to discover important patterns, biomarkers, and treatment strategies that can have a significant impact on cancer research and oncology. In addition, the identification of previously successfully treated patients supports oncologists in making treatment decisions for a new patient who is clinically or molecularly similar to the previous patient. Objective: The planned review aims to systematically summarize, map, and describe existing evidence to understand how patient similarity is defined and used in cancer research and clinical care. Methods: To systematically identify relevant studies and to ensure reproducibility and transparency of the review process, a comprehensive literature search will be conducted in several bibliographic databases, including Web of Science, PubMed, LIVIVIVO, and MEDLINE, covering the period from 1998 to February 2024. After the initial duplicate deletion phase, a study selection phase will be applied using Rayyan, which consists of 3 distinct steps: title and abstract screening, disagreement resolution, and full-text screening. To ensure the integrity and quality of the selection process, each of these steps is preceded by a pilot testing phase. This methodological process will culminate in the presentation of the final research results in a structured form according to the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) flowchart. The protocol has been registered in the Journal of Medical Internet Research. Results: This protocol outlines the methodologies used in conducting the scoping review. A search of the specified electronic databases and after removing duplicates resulted in 1183 unique records. As of March 2024, the review process has moved to the full-text evaluation phase. At this stage, data extraction will be conducted using a pretested chart template. Conclusions: The scoping review protocol, centered on these main concepts, aims to systematically map the available evidence on patient similarity among patients with cancer. By defining the types of data sources, approaches, and methods used in the field, and aligning these with the research questions, the review will provide a foundation for future research and clinical application in personalized cancer care. This protocol will guide the literature search, data extraction, and synthesis of findings to achieve the review’s objectives.
CRIS-Team Scopus Importer:2024-09-13
Keywords: cancer research; cancer similarity metrics; patient similarity; patient similarity applications; precision medicine; scoping review protocol

Mapping the Entire Record-An Alternative Approach to Data Access from Medical Logic Modules - Kraus, Stefan; Toddenroth, Dennis; Staudigel, Martin; Rödle, Wolfgang; Unberath, Philipp; Griebel, Lena; Prokosch, Hans-Ulrich; Mate, Sebastian (Applied Clinical Informatics, 2020)
OBJECTIVES: This study aimed to describe an alternative approach for accessing electronic medical records (EMRs) from clinical decision support (CDS) functions based on Arden Syntax Medical Logic Modules, which can be paraphrased as "map the entire record." METHODS: Based on an experimental Arden Syntax processor, we implemented a method to transform patient data from a commercial patient data management system (PDMS) to tree-structured documents termed CDS EMRs. They are encoded in a specific XML format that can be directly transformed to Arden Syntax data types by a mapper natively integrated into the processor. The internal structure of a CDS EMR reflects the tabbed view of an EMR in the graphical user interface of the PDMS. RESULTS: The study resulted in an architecture that provides CDS EMRs in the form of a network service. The approach enables uniform data access from all Medical Logic Modules and requires no mapping parameters except a case number. Measurements within a CDS EMR can be addressed with straightforward path expressions. The approach is in routine use at a German university hospital for more than 2 years. CONCLUSION: This practical approach facilitates the use of CDS functions in the clinical routine at our local hospital. It is transferrable to standard-compliant Arden Syntax processors with moderate effort. Its comprehensibility can also facilitate teaching and development. Moreover, it may lower the entry barrier for the application of the Arden Syntax standard and could therefore promote its dissemination.
CRIS-Team Scopus Importer:2020-05-22

MIRACUM-Pipe: An Adaptable Pipeline for Next-Generation Sequencing Analysis, Reporting, and Visualization for Clinical Decision Making - Metzger, Patrick; Hess, Maria Elena; Blaumeiser, Andreas; Pauli, Thomas; Schipperges, Vincent; Mertes, Ralf; Christoph, Jan; Unberath, Philipp; Reimer, Niklas; Scheible, Raphael; Illert, Anna L.; Busch, Hauke; et al. (Cancers, 2023)
(1) Background: Next-generation sequencing (NGS) of patients with advanced tumors is becoming an established method in Molecular Tumor Boards. However, somatic variant detection, interpretation, and report generation, require in-depth knowledge of both bioinformatics and oncology. (2) Methods: MIRACUM-Pipe combines many individual tools into a seamless workflow for comprehensive analyses and annotation of NGS data including quality control, alignment, variant calling, copy number variation estimation, evaluation of complex biomarkers, and RNA fusion detection. (3) Results: MIRACUM-Pipe offers an easy-to-use, one-prompt standardized solution to analyze NGS data, including quality control, variant calling, copy number estimation, annotation, visualization, and report generation. (4) Conclusions: MIRACUM-Pipe, a versatile pipeline for NGS, can be customized according to bioinformatics and clinical needs and to support clinical decision-making with visual processing and interactive reporting.
CRIS-Team Scopus Importer:2023-08-11
Keywords: bioinformatics; computational biology; molecular tumor board; next-generation sequencing; pipeline; precision oncology; software; somatic variant calling; workflow

Requirements analysis and specification for a molecular tumor board platform based on CBIoPortal - Buechner, Philipp; Hinderer, Marc; Unberath, Philipp; Metzger, Patrick; Boeker, Martin; Acker, Till; Haller, Florian; Mack, Elisabeth; Nowak, Daniel; Paret, Claudia; Schanze, Denny; von Bubnoff, Nikolas; et al. (Diagnostics, 2020)
Clinicians in molecular tumor boards (MTB) are confronted with a growing amount of genetic high-throughput sequencing data. Today, at German university hospitals, these data are usually handled in complex spreadsheets from which clinicians have to obtain the necessary information. The aim of this work was to gather a comprehensive list of requirements to be met by cBioPortal to support processes in MTBs according to clinical needs. Therefore, oncology experts at nine German university hospitals were surveyed in two rounds of interviews. To generate an interview guideline a scoping review was conducted. For visual support in the second round, screenshot mockups illustrating the requirements from the first round were created. Requirements that cBioPortal already meets were skipped during the second round. In the end, 24 requirements with sometimes several conceivable options were identified and 54 screenshot mockups were created. Some of the identified requirements have already been suggested to the community by other users or are currently being implemented in cBioPortal. This shows, that the results are in line with the needs expressed by various disciplines. According to our findings, cBioPortal has the potential to significantly improve the processes and analyses of an MTB after the implementation of the identified requirements.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Clinical; precision medicine; computational biology; molecular tumor board; cBioPortal; requirements analysis; neoplasms; Computer-assisted; decision support systems; Decision making

Searching of Clinical Trials Made Easier in cBioPortal Using Patients' Genetic and Clinical Profiles - Unberath, Philipp; Mahlmeister, Lukas; Reimer, Niklas; Busch, Hauke; Boerries, Melanie; Christoph, Jan (Applied Clinical Informatics, 2022)
Background Molecular tumor boards (MTBs) cope with the complexity of an increased usage of genome sequencing data in cancer treatment. As for most of these patients, guideline-based therapy options are exhausted, finding matching clinical trials is crucial. This search process is often performed manually and therefore time consuming and complex due to the heterogeneous and challenging dataset. Objectives In this study, a prototype for a search tool was developed to demonstrate how cBioPortal as a clinical and genomic patient data source can be integrated with ClinicalTrials.gov, a database of clinical studies to simplify the search for trials based on genetic and clinical data of a patient. The design of this tool should rest on the specific needs of MTB participants and the architecture of the integration should be as lightweight as possible and should not require manual curation of trial data in advance with the goal of quickly and easily finding a matching study. Methods Based on a requirements analysis, interviewing MTB experts, a prototype was developed. It was further refined using a user-centered development process with multiple feedback loops. Finally, the usability of the application was evaluated with user interviews including the thinking-aloud protocol and the system usability scale (SUS) questionnaire. Results The integration of ClinicalTrials.gov in cBioPortal is achieved by a new tab in the patient view where the genomic profile for the search is prefilled and additional parameters can be adjusted. These parameters are then used to query the application programming interface (API) of ClinicalTrials.gov. The returned search results subsequently are ranked and presented to the user. The evaluation of the application resulted in an SUS score of 83.5. Conclusion This work demonstrates the integration of cBioPortal with ClinicalTrials.gov to use clinical and genomic patient data to search for appropriate trials within an MTB.
CRIS-Team Scopus Importer:2022-04-15
Keywords: clinical decision support; clinical trial; genetic alteration; genomics; molecular tumor board; trial matching